Inhabiting Relingos: Horizontal Harlem, Told Vertically - Hannah Huxley (Janeway JS, 2019)
From the period of its development during the late 19th century, Harlem has experienced rapid growth, both spatially and aesthetically. A rich variety of literature has emerged, and continues to emerge, from its diverse and multicultural scene, prompting a new critical approach in academic scholarship. This thesis explores the transnational impact of Harlem, from the emergence of its cultural renaissance to its contemporary aesthetic presence. Specifically, it will consider the recently published work of Latin-American author Valeria Luiselli, discussing the transnational dimensions of her novel, and the re-definition of Harlem as a space without aesthetic or spatial boundaries.